Essays on new institutional economics - Richter, Rudolf (Springer International Publishing Imprint: Springer, 2015)
This collection of essays comprises some of Rudolf Richter's important contributions to research on New Institutional Economics (NIE). It deals with the central idea, principles, and methodology of New Institutional Economics and explores its relation to sociology and law. Other chapters examine applications of NIE to various microeconomic and macroeconomic issues in the face of uncertainty, from entrepreneurship to the euro crisis.